Internalisasi Jiwa Sosial Masyarakat Bagi Generasi Milenial Melalui Nilai-Nilai Al-Qur’an - Andika, Andika (Jurnal Ilmiah Ilmu Ushuluddin, 2022)
The social spirit of society and the values of the Qur'an are two interrelated sides. The current phenomenon shows that the social spirit of society has begun to be fragile and faded for the millennial generation due to the flow of globalization. If one of the two is strengthened then both can be saved. Therefore, this study wants to reveal the values of the Qur'an in the form of the value of brotherhood, the value of knowing each other, the value of equality, and the value of simplicity and generosity contained in the social soul of society. This research analyzes the problems above using a descriptive qualitative approach through a literature study. The results of this study explain that the values of the Qur'an contained in the social soul of the community are able to become a formula for internalizing the social soul of society for the millennial generation. In the end, this research provides a solution in the form of holding taklim majlis, education, congregational prayers, social harmony forums, and mutual cooperation culture which are considered to be effective solutions in growing the social spirit of society for the millennial generation through the values of the Qur'an